Studi Kelayakan Rencana Pendirian Pop Hotel Di Yogyakarta oleh PT. Heidi Cahaya Berkat - Pandanwangi, Nurina; , Dra. Wuryaningsih Dwi Lestari, MM (2016)
This study aims to determine the feasibility of the establishment of POP Hotel in the heart of Yogyakarta Special Region by PT. Heidi Cahaya berkat. Seeing the number of tourists in Yogyakarta are increasing every year and the attractiveness of tourism in Yogyakarta are constantly evolving and new objects popping visited by many tourists, but less supported by the availability of sufficient accommodation lure tourists for longer stay. The feasibility study consists of market aspects, technical aspects, juridical and organizational aspects, financial aspects, risk analysis and SWOT analysis. On the financial aspect implemented investment appraisal Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR) Benefit Cost Ratio (BCR). From the calculation of payback period will be returned within a period of 5 years and 8 months, the investment over the age limit of 11 years, the Net Present Value positive value of Rp 7,511,605,301., Internal Rate of Return is 17%, and the Benefit Cost Ratio totaled 1 , 12. Then the payback period is less than the maximum limit of its economic life, the Net Present Value which is positive, Internal Rate of Return is greater than the discount factor used, and the Benefit Cost Ratio greater than 1, the establishment of POP Hotel in the Region Outstanding Yogyakarta by PT. Heidi Cahaya Berkat feasible.